2020
DOI: 10.1186/s12966-020-0913-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical activity programs on sleep outcomes in older adults: a systematic review

Abstract: Background: One in two older adults report sleep problems, which not only cause fatigue, but also negatively affect general functioning, activities of daily living, and physical and mental health. Although it is known that physical activity is positively associated with sleep in older adults, the effects of physical activity programs on sleep in older adults has not been reviewed. The aim of this systematic review was to systematically review the effects of physical activity programs on sleep in generally heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 100 publications
4
105
3
5
Order By: Relevance
“…Moreover, supporting low and high sleepers to be more physically active when awake may have an additional secondary benefit associated with improved sleep. Although inconclusive, there is emerging evidence in older adult populations indicating that an increase in physical activity can be associated with better sleep duration and sleep quality (47,48). We found that younger age was associated with a greater likelihood for allocation to a balanced activity profile; however, despite being a statistically significant factor, age was only marginally associated with profile allocation.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, supporting low and high sleepers to be more physically active when awake may have an additional secondary benefit associated with improved sleep. Although inconclusive, there is emerging evidence in older adult populations indicating that an increase in physical activity can be associated with better sleep duration and sleep quality (47,48). We found that younger age was associated with a greater likelihood for allocation to a balanced activity profile; however, despite being a statistically significant factor, age was only marginally associated with profile allocation.…”
Section: Discussionmentioning
confidence: 56%
“…During this period, the actual frequency of nightshifts for the healthcare workers was not as high as usual (2.97 ± 1.37 vs. 4.99 ± 0.35 days, respectively). Furthermore, because the healthcare workers still had to work a certain number of days, they still participated in moderate physical activity and experienced moderate not excessive fatigue, which might have led to better sleep quality [ 21 ]. Another possible reason was that an appropriate work time ensured the proficiency of clinical work [ 22 ], which was also supported by another observation in this study that the years of work experience were negatively associated with sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…This study reconfirmed protective effects of exercise on residents' sleep quality during the COVID-19 epidemic. Previous studies have analyzed protective mechanisms of exercise on sleep conditions in different populations [ [27] , [28] , [29] ]. To contain the outbreak and spread of the disease, China adopted strict preventive and control measures such as isolation of close contacts and city lockdowns during the outbreak [ 3 , 4 ], which will inevitably restrict travels and outdoor exercise of Chinese residents.…”
Section: Discussionmentioning
confidence: 99%